1977
DOI: 10.1017/s0022149x0000763x
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides ratti: 1. Parasitological observations on primary and secondary infections in the small intestine of rats

Abstract: Adult Strongyloides ratti were expelled from the small intestine of rats starting 14—18 days after a primary infection. In a secondary infection very few adult worms developed and most of these were expelled before day 14. At the time of expulsion the worms migrated posteriorly in the intestine and their size decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 17 publications
3
15
0
1
Order By: Relevance
“…The data are summarized in Figure 1. The course of infection in this strain is basically similar to that described in the inbred WAG and outbred Wistar and CFHB strains (Moqbel & Denham 1977, Moqbel & Wakelin 1979, in that worm loss commenced between days 16 and 20 with corresponding reductions in worm size and fecundity and a shift of population in to the posterior small intestine.…”
Section: Transfer Of Immunity With Imlnc Taken At Different Times Dursupporting
confidence: 73%
See 1 more Smart Citation
“…The data are summarized in Figure 1. The course of infection in this strain is basically similar to that described in the inbred WAG and outbred Wistar and CFHB strains (Moqbel & Denham 1977, Moqbel & Wakelin 1979, in that worm loss commenced between days 16 and 20 with corresponding reductions in worm size and fecundity and a shift of population in to the posterior small intestine.…”
Section: Transfer Of Immunity With Imlnc Taken At Different Times Dursupporting
confidence: 73%
“…Details of the parasite, the methods used for infecting rats, for recovering and counting adult worms and for determining their size and fecundity have been described earlier (Moqbel & Denham 1977, Moqbel & Wakelin 1979. Values for worm lengths (in mm) and fecundities (expressed as number of eggs in utero per female worm) were based on examination of 1G30 randomly selected, glutaraldehyde-fixed worms from each group.…”
Section: The Parasitementioning
confidence: 99%
“…Several investigators have shown that ELISA (5,28), indirect immunofluorescence tests (17), and the histamine release assay (10) with Strongyloides ratti larval antigens are essentially as sensitive as those using S. stercoralis for the detection of parasite-specific IgG and IgE antibodies. S. ratti is readily maintained in laboratory rats (27), and it may represent the most practical source of antigens for most clinical applications of these serologic tests.…”
Section: Resultsmentioning
confidence: 99%
“…Cette agression traduit la persistance d'une migration larvaire soulignée par Jarrett et Urquhart (1968), Moqbel et Denham (1977) et particulièrement étudiée par Taliaferro et Sarles (1939) avec N. muris. Parmi les résultats publiés par ces derniers auteurs, nous retenons ceux correspondant à une infestation et à une réin-festation selon des modalités qui se rapprochent le plus des conditions expérimentales dans lesquelles nous nous sommes placés : réinfestation par 5 000 larves, 6 à 8 semaines après 3 infestations à 3 jours d'intervalle par 5 000 larves.…”
Section: Discussionunclassified